DICTIONARY OF COVID-19 TERMS: ENGLISH–FRENCH–ARABIC” TERBITAN ALESCO 2020: PENGARUH COVID-19 TERHADAP PERUBAHAN MAKNA BAHASA ARAB (KAJIAN SEMANTIK) - Junaedi, J; Alfatawi, Ahmad Talkhis; Fathani, Ahmad; Nisa', Khoirun (STIQ Amuntai, 2023)
Language and phenomena are two things that cannot be separated. New phenomena will give birth to new languages as well. The Covid-19 pandemic is undoubtedly not a phenomenon that can be considered small. Of course, COVID-19's contribution to the treasures of language will be substantial. This research will try to dissect the terms about COVID-19 listed in the Dictionary of Covid-19 Terms: English – French – Arabic, an electronic dictionary published by ALESCO (Arab et al. Organization). This research uses a descriptive qualitative method with a semantic change approach in the style of Mukhtar Umar. The results obtained from this research are that the terms in this dictionary are not the production of new words but rather old words labeled with new meanings. Researchers found four words that experienced changes in meaning, two in the form of a shift in meaning, one in the form of an expansion of definition, and one in the form of a narrowing of meaning.